COMPARABILITY OF ITEM PARAMETER INDICES OF 2019 SENIOR SCHOOL CERTIFICATE PHYSICS MULTIPLE-CHOICE EXAMINATIONS AMONG OSUN STATE SECONDARY SCHOOL STUDENTS - Owoeye, Oluwasola Damilola; ADEDIWURA, Alaba Adeyemi (African Journal of Behavioural and Scale Development Research, 2025)
The study assessed the difference in average item difficulty parameters in public examinations- Senior School Certificate Examination and National Examination Council which were conducted in 2019. The aspect of questions that were accessed in this study were Physics multiple-choice items that focus on secondary school students in Osun State. Hence, the study compared the comparison that exists between item difficulty and students’ ability based on Physics examination items. More so, standard errors of measurements that exist in the WAEC and NECO were accessed. The survey research design is adopted as it helps in the gathering of information from participants in their environment. All senior secondary school students from all the senatorial districts in Osun State made up the study population. Osun State has 1,494 senior secondary schools of which 1,100 and 394 schools are private and public respectively. The population of Senior Secondary Three (SSS III) students consisted of a total number of 17,784 as of the 2022/2023 session. From the population, a total of 1200 SSS III were selected and engaged in the study with the aid of the multistage sampling procedure. The 3-parameter logistic model as presented has the lowest values for all of the information criteria (AIC = 82986.44, SABIC = 83330.90, HQ = 83331.57, BIC = 83902.65). However, for the WAEC data, the table shows that the 4-parameter logistic (4PL) model has the lowest values for all of the information criteria (AIC = 70591.57, SABIC = 70974.30, HQ = 70975.04, BIC = 71609.58). More so, WAEC items were more difficult () than the item difficulties of NECO () as shown in the table. It is shown that examinees performed better in WAEC (mean = 0.004, STD = 0.935) than they performed in NECO (mean = 0.002, STD = 0.948). In conclusion, there was more difficulty in WAEC items compared to NECO items in the year 2019. However, this difference was not statistically significant, while the examinees generally performed slightly better in WAEC than in NECO.